Examination of Electrodynamic Forces in High Voltage Disconnector Related to the Short-Circuit Current Using the Digital Twin Technology - Michal Szulborski; Sebastian Lapczynski; Lukasz Kolimas; Lukasz Kozarek; Hubert Cichecki; Przemyslaw Sul; Maciej Owsinski; Przemyslaw Berowski; Dariusz Baczynski; Marcin Wesolowski (IEEE Access, 2024)
Paper concerns the novel modelling technology called digital twin in aspect of physical phenomenon simulation analysis. Digital twin model concerning electrodynamic forces in three-phase high voltage disconnector was presented, validated and discussed. Experiences related to laboratory work and measurement of electrodynamic forces clearly showed that often, despite the use of modern computing machines, the research process is hard, very expensive and values of electrodynamic forces are almost impossible to measure in real scale conditions. Hence the idea to use very advanced field models minimized to a reduced order model (ROM), using the digital twin technology seemed valid and rendered possibilities for advancements concerning this type of research. Due to the large weight of devices (chokes, transformers, disconnectors) on high-voltage networks it is often time-consuming or even impossible to perform the entire simulation. Proposed modelling approach helps to obtain results from very complex models also for long-term thermal tests. The reduced order model can be used not only by researchers, but also in the development departments of enterprises. Digital twin model results were compared and validated with values derived from short-circuit tests made in Institute of Power Engineering, Research Institute.